HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA LANSIA YANG MENDERITA PENYAKIT HIPERTENSI DI LABORATORIUM KLINIK PRODIA CABANG MAKASSAR - Andi Irmayanti (Jurnal Berita Kesehatan, 2022)
ABSTRACT Background: The prevalence of hypertension in Africa is 27% and of the total population,in Southeast Asia is the highest incidence of hypertension at 25% (Kemenkes RI, 2020). Hypertensive patients who visit Makassar branch of Prodia clinic every year, in 2019 there were 663 people, in 2020 there were 575, in 2021 there were 744 people while in January - March 2022 there were 199 people. Research Objectives: The relationship between family support and medication adherence in elderly who suffer from hypertension is known in Prodia Clinical Laboratory Makassar Branch. Research Methods: This type of study is a cross sectional study. The population in this study were all hypertensive patients in the elderly who came to check themselves at Prodia Clinical Laboratory Makassar Branch. And the sample technique used using accidental sampling, so that the number of samples in this study as many as 39 samples. Research Results: The results of this study using the chi-square statistical test obtained the value of p = 0.000, which means that it is smaller than the ⑴ (0.05). Thus, the research hypothesis is accepted, meaning that there is a relationship between family support and adherence to taking hypertension medication in the elderly who visit the Makassar branch of Prodia laboratory clinic.Suggestions: It is expected that it can increase and maintain attention, and support to the elderly in the role of family both in informational, psychological and other support.Makassar city government. Keywords :Family support and medication adherence